Capacitors
By introducing single-element oxide particles of magnesium, rare earth elements and manganese into the dielectric layer, the problem of heat generation and insulation reduction of the laminated capacitor under long-term voltage application is solved, and higher heat dissipation and reliability are achieved.
Patent Information
- Application Number
- CN202080065591.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-26
- Filing Date
- 2020-09-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-09-10
AI Technical Summary
The existing stacked capacitors are prone to heat when voltage is applied and long-term use, resulting in a decrease in insulation and reliability.
Single-element oxide particles of magnesium, rare earth elements and manganese are introduced into the dielectric layer to improve the heat dissipation of the dielectric layer and thereby suppress the increase in the capacitor temperature.
By improving the heat dissipation of the dielectric layer, the high temperature load life of the capacitor is extended, the high electrostatic capacitance is maintained, and the reliability of the capacitor is improved.
Smart Images

Figure CN114424306B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a stacked capacitor. Background Art
[0002] An example of the prior art is described in Patent Document 1.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-132056 Summary of the invention
[0006] The capacitor disclosed herein comprises a capacitor body in which a plurality of dielectric layers and internal electrode layers are alternately stacked, wherein the dielectric layers are mainly composed of a plurality of crystal grains having barium titanate as a main component, and contain magnesium, a rare earth element, and manganese, wherein at least one of the magnesium, the rare earth element, and the manganese exists in the form of single element oxide particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] The objects, features, and advantages of the present disclosure will become more apparent from the following detailed description and accompanying drawings.
[0008] Figure 1 It is a perspective view of the appearance of a capacitor shown as an example of an embodiment.
[0009] Figure 2 yes Figure 1 Sectional view along line ii-ii.
[0010] Figure 3 Yes Figure 2 An enlarged cross-sectional view of part P1. DETAILED DESCRIPTION
[0011] First, as a capacitor formed based on the capacitor disclosed in the present invention, in recent years, multilayer capacitors (hereinafter referred to as capacitors) have been developed with thinner dielectric layers and internal electrode layers for miniaturization and higher capacitance.
[0012] Thinning the dielectric layer in a capacitor is one of the means to increase the electrostatic capacitance of the capacitor. However, when the thickness of the dielectric layer becomes thinner, it is difficult to ensure insulation. When a voltage is applied to a capacitor and this state is allowed to continue for a long time, the capacitor generates heat, the temperature rises, and the reliability is easily reduced. That is, when the state of driving an electronic device and applying a voltage to a capacitor continues, the temperature of the capacitor gradually rises due to the continuous application of voltage. When taking the reliability test as an example, the capacitor is continuously subjected to a high temperature load life test.
[0013] The following is based on Figure 1 to Figure 3 The capacitor of the embodiment is described. It should be noted that the present disclosure is not limited to the specific embodiments described below. The present disclosure may include various forms as long as it conforms to the spirit or scope of the general disclosure concept defined by the appended claims.
[0014] like Figure 1 As shown in FIG. 1 , the capacitor of the embodiment includes a capacitor body 1 and external electrodes 3 provided on the end surfaces thereof. Figure 2 As shown in FIG. 1 , the capacitor body 1 includes a dielectric layer 5 and an internal electrode layer 7. The dielectric layer 5 and the internal electrode layer 7 are alternately stacked in a plurality of layers. Figure 2 In the figure, the number of laminated dielectric layers 5 and internal electrode layers 7 is simplified to a few layers, but the number of laminated dielectric layers 5 and internal electrode layers 7 is actually several hundred layers. The external electrode 3 is electrically connected to the internal electrode layer 7 .
[0015] The dielectric layer 5 includes, as a main body, a plurality of crystal grains 9 having barium titanate as a main component. In other words, the dielectric layer 5 includes, as a mother phase 5A, a plurality of crystal grains 9 having barium titanate as a main component. Here, the main component refers to the component contained in the largest amount in the crystal grains 9. Having barium titanate as the main component means a state in which the content of titanium and barium in the crystal grains 9 is greater than the content of other components. The main body refers to the part of the dielectric layer 5 that has the highest volume proportion and represents the main function. For example, in a capacitor, it is a sintered body of crystal grains that mainly bears the electrostatic capacitance. The meaning of the mother phase 5A is similar to the above-mentioned main body, but if we have to say it, it refers to the crystalline phase that exists in the dielectric layer 5 in the highest volume proportion. For example, it refers to a crystalline phase that occupies a volume proportion of more than 60% in the dielectric layer 5.
[0016] In the capacitor of the embodiment, the dielectric layer 5 contains magnesium, rare earth elements, and manganese in addition to barium titanate. In addition, in the dielectric layer 5, at least one element among magnesium (Mg), rare earth elements (RE), and manganese (Mn) exists in the form of single element oxide particles 11. Here, the single element oxide particles 11 refer to, for example, in the case of magnesium (Mg), crystals having magnesium oxide (MgO) as a main component that exist in the dielectric layer 5 without forming a composite oxide with other metal oxides. The state in which one element exists in the dielectric layer 5 in the form of single element oxide particles 11 refers to, for example, when performing powder X-ray diffraction of the dielectric layer 5, it is at a level that can confirm the diffraction peak of the metal oxide constituting the oxide particle 11. The metal oxide is a state containing only one metal element.
[0017] In addition, when the oxide particles 11 seen in the cross section of the dielectric layer 5 are subjected to elemental analysis, there is a case where the count of the corresponding element is the highest and its count is more than 10 times that of other elements. Hereinafter, oxide particles 11 containing at least one element of magnesium (Mg), rare earth elements (RE) and manganese (Mn) in the form of single element oxides are sometimes referred to as oxide particles 11. In addition, crystal grains 9 with barium titanate as the main component are sometimes referred to as main crystal grains 9. The particle size of the main crystal grains 9 can be greater than 0.05 μm and less than 0.5 μm. As rare earth elements (RE), it is equivalent to elements with atomic numbers 57 to 71 shown as lanthanide elements in the periodic table. Among them, preferred are dysprosium (Dy), yttrium (Y), erbium (Er), holmium (Ho), Yb (ytterbium) and Tb (terbium). The chemical formulas of dysprosium (Dy), yttrium (Y), erbium (Er), holmium (Ho), Yb (ytterbium) and Tb (terbium) when they form single element oxide particles 11 are Dy2O3, Y2O3, Er2O3, Ho2O3, Yb2O3 and Te2O3. Manganese (Mn) is MnO or Mn2O3.
[0018] The thermal conductivity of the oxide particles 11 containing magnesium, rare earth elements, and manganese in the form of single element oxides is higher than that of the barium titanate grains 9 which are composite oxides. Therefore, in the dielectric layer 5 in which the barium titanate grains 9 are the parent phase 5A, if at least one of these magnesium, rare earth elements, and manganese exists in the form of single element oxide particles 11, the heat dissipation of the dielectric layer 5 in which the main grains 9 are the parent phase 5A can be improved.
[0019] When a capacitor is in a state where a DC voltage is continuously applied, the capacitor heats up over time. When the temperature of the capacitor rises, defects such as oxygen vacancies existing in the dielectric layer 5 tend to move in the dielectric layer 5. As a result, the insulation of the dielectric layer 5 tends to decrease. In addition, the high temperature load life is shortened.
[0020] In contrast, in the capacitor of the embodiment, as described above, the dielectric layer 5 contains oxide particles 11 having a higher thermal conductivity than barium titanate. Thus, the dielectric layer 5 can improve heat dissipation. As a result, even when a DC voltage is continuously applied to the capacitor, the temperature rise of the capacitor can be suppressed. In this way, the high temperature load life of the capacitor can be extended.
[0021] In this case, in the capacitor of the embodiment, the oxide particles 11 may have a diameter D that is equivalent to the average particle size of the main crystal grains 9. The diameter of the oxide particles 11 may be, for example, not less than 0.15 μm and not more than 0.3 μm. The not less than 0.15 μm and not more than 0.3 μm indicated as the diameter of the oxide particles 11 refers to the average particle size of each oxide particle 11 contained in the dielectric layer 5, but in this case, oxide particles having a particle size of not less than 0.15 μm and not more than 0.3 μm may be included at a number frequency of not less than 90%. If the average particle size of the oxide particles 11 is not less than 0.15 μm and not more than 0.3 μm, the particle size of the oxide particles 11 becomes close to the particle size of the main crystal grains 9. If the size of the oxide particles 11 becomes close to that of the main crystal grains 9, as shown in FIG. Figure 3 As shown, the oxide particles 11 and the main crystal grains 9 are likely to be in contact with each other at the dihedral grain boundaries 13. As a result, the contact area between the oxide particles 11 and the main crystal grains 9 increases.
[0022] Here, the average particle size of the oxide particles 11 is obtained as follows. First, the capacitor is ground or cut to expose the cross section of the capacitor body 1. Then, the exposed cross section of the capacitor body 1 is ground. Then, the cross section of the capacitor body 1 after grinding is observed, for example, using a scanning electron microscope equipped with an analyzer, and a photograph of a specific area is taken. At this time, the main components of the main crystal grains 9 and the oxide particles 11 are determined by analyzing the components of the main crystal grains 9 and the oxide particles 11. Then, a region containing oxide particles 11 and 200 to 300 main crystal grains is selected in the photograph. Then, the contours of the plurality of oxide particles 11 present in the region containing 200 to 300 main crystal grains are obtained from the photograph. Then, the contours of each oxide particle 11 are image processed, and the area of the circle is obtained from the contour. Then, the diameter is obtained from the area of the circle. Finally, the diameters obtained are added together to obtain the average value. In this way, the average particle size of the obtained oxide particles can be obtained. In addition, the same method is used for the diameter of the main crystal grains 9 and the average particle size.
[0023] like Figure 3As shown, when the cross section of the dielectric layer 5 is viewed from above, for example, when the main crystal grain 9 is a circle or a polygon close to a circle, the oxide particles 11 may include oxide particles having a shape equivalent to the grain boundary phase 15 formed by a plurality of main crystal grains 9 adjacent to each other. Here, the shape of the oxide particle 11 equivalent to the shape of the grain boundary phase 15 refers to the shape of the dielectric layer 5 when the cross section is observed. The main crystal grain 9 is a circle, which means that the outline of the main crystal grain 9 is circular as a whole, and when the longest diameter in the main crystal grain 9 is set as the maximum diameter D1 and the direction perpendicular to the direction of the maximum diameter D1 is set as the minimum diameter D2, the ratio D1 / D2 is greater than 1 and less than 1.1. The main crystal grain 9 is a polygon, which means that at least two straight edges are visible in a part of the outline of the main crystal grain 9.
[0024] The shape of the oxide particle 11 corresponding to the shape of the grain boundary phase 15 refers to, for example, the shape of the region between two or more adjacent main grains 9. In other words, it is a shape that fills the space between two or more adjacent main grains 9. The shape of the oxide particle 11 corresponding to the shape of the grain boundary phase 15 sometimes includes shapes that are difficult to assign specific names to, and the following shapes can be cited as examples. In this case, symbols are added to the terms representing the shape of the oxide particle 11. For example, Figure 3 As shown, the shape is a circular shape (symbol 11a), a polygonal shape (11b), a triangular shape (11c), a quadrilateral shape (11d), an elliptical shape (11e), a tumbler shape (11f), an arrow shape (11g), a concave-convex shape (11h) formed by connecting a neck portion (11ha) and a trunk portion (11hb). In addition, the dielectric layer 5 may also include oxide particles 11 in a shape formed by combining a plurality of shapes with additional symbols 11a to 11h. Here, the tumbler shape 11f refers to a shape formed by combining a large particle portion 11fa with a large volume and a small particle portion 11fb with a smaller volume than the large particle portion 11fa. The arrow shape 11g refers to a shape that is basically a triangle, but even if one end is sharp, the opposite side is a rounded shape or a flat surface. In this case, the arrow shape 11g also includes a shape in which two of the three sides are slightly curved convexly outward. The concavoconvex shape 11h formed by connecting the constricted portion 11ha and the trunk portion 11hb is basically a long and narrow strip shape, but the constricted portion 11ha and the trunk portion 11hb may be connected in the longitudinal direction. In this case, the trunk portion 11hb may also include a shape that bulges outward.
[0025] If the shape of the oxide particles 11 is equivalent to the shape of the grain boundary phase 15 formed by the plurality of main crystal grains 9 adjacent to each other, the oxide particles 11 may be in a state of partially surrounding the periphery of the main crystal grains 9. In addition, by interposing the oxide particles 11 between the plurality of main crystal grains 9, the contact area with the adjacent plurality of main crystal grains 9 can be indirectly increased. This can improve the thermal conductivity of the capacitor.
[0026] In the capacitor of the embodiment, the proportion of the oxide particles 11 contained in the dielectric layer 5 can be greater than 0.5% and less than 5%, and in particular, can be greater than 1.5% and less than 3%. As shown below, the proportion of the oxide particles 11 shown here is a value obtained based on the diffraction intensity ratio of the X-ray pattern of the powder obtained by pulverizing the dielectric layer 5 or the capacitor. In this case, after obtaining the diffraction intensity I0 of the main peak (index 110) of the barium titanate constituting the main crystal grain 9 and the diffraction intensity I1 of the main peak (index 111) of the oxide particles 11, the diffraction intensity ratio I1 / I0 is obtained. In this case, if the diffraction intensity ratio is greater than 0.5%, the effect of thermal conduction of the oxide particles 11 on the dielectric layer 5 can be obtained. If the diffraction intensity ratio is less than 3%, since the decrease in the relative dielectric constant of the dielectric layer 5 is suppressed, the capacitor can maintain a high electrostatic capacitance.
[0027] In the capacitor of the embodiment, the oxide particles 11 may be present in the region other than the internal electrode layer 7 in the capacitor body 1. If the oxide particles 11 are present in the entire region other than the internal electrode layer 7 in the capacitor body 1, the heat conductivity is increased at any position of the capacitor body 1, and thus the heat dissipation can be further improved.
[0028] Next, the manufacturing method of the capacitor of the embodiment is described. The capacitor of the embodiment can be manufactured by a conventional manufacturing method of a capacitor, except that raw material powders that have been pre-fired in a predetermined ratio are added to the ceramic green sheet for forming the dielectric layer 5 as additives, namely raw material powders of magnesium, rare earth elements and manganese, and the heating rate during the main firing is higher than usual and the firing is performed in a short time. If the raw material powder that has been pre-fired in advance is used as the additive added to the raw material powder of barium titanate, the additive is likely to remain in the dielectric layer 5 directly in the form of a single element metal oxide after the main firing. In this case, the heating rate during the main firing can be increased within a range that does not damage the sinterability of the dielectric layer 5. Since the time that the capacitor body 1 is exposed to the high temperature environment is shortened, the proportion of the additive remaining directly in the form of a single element metal oxide after the main firing is increased. In this way, crystal grains 9 with barium titanate as the main component and oxide particles 11 in which at least one element among magnesium, rare earth elements and manganese exists in the form of a single element oxide can be present in the dielectric layer 5.
[0029] Example
[0030] The following is a detailed description of capacitor production and characteristic evaluation. First, barium titanate powder and glass powder are prepared as raw material powders for preparing dielectric powders. In the barium titanate powder, a raw material powder with an average particle size of 0.05 μm is used. In the glass powder, a powder with a composition of SiO2=55, BaO=20, CaO=15, and Li2O=10 (mol%) is used. Magnesium oxide powder and manganese carbonate powder are prepared as raw material powders for additives. In addition, rare earth element oxide powders are prepared. The composition of the rare earth element oxide powders is shown in Table 1. The average particle size of magnesium oxide powder and manganese carbonate powder is 0.1 μm. The average particle size of the rare earth element oxide powder is 0.05 μm. Among these raw material powders, in samples No. 1 to No. 20, powders pre-fired in air at a maximum temperature of 850°C and a holding time of 2 hours are used as rare earth element oxide powders. In the sample No. 21, a powder having an average particle size of 0.1 μm was used as the Y2O3 powder. The Y2O3 powder used in the sample No. 21 was a raw material powder that was not subjected to a calcination treatment.
[0031] The composition of the dielectric powder is as follows: 0.5 mol of magnesium oxide powder converted to MgO and 0.5 mol of manganese carbonate powder converted to MnO are added to 100 mol of barium titanate powder, and 1 part by mass of glass powder is added to 100 parts by mass of the barium titanate powder. The addition amount of the oxide powder of the rare earth element is shown in Table 1.
[0032] Next, an organic vehicle was mixed with the dielectric powder, and the prepared slurry was used to prepare a ceramic green sheet with an average thickness of 2.8 μm by a doctor blade method. As a resin contained in the organic vehicle when preparing the ceramic green sheet, a butyral resin was used. The amount of butyral resin added was 10 parts by mass relative to 100 parts by mass of the barium titanate powder. As a solvent, a solvent in which ethanol and toluene were mixed at a mass ratio of 1:1 was used. As a conductor paste for forming an internal electrode pattern, a conductor paste containing nickel powder was used.
[0033] Next, a conductor paste is printed on the ceramic green sheet to produce a pattern sheet. Next, 400 layers of pattern sheets are stacked to produce a core laminate. Next, ceramic green sheets are stacked on the upper and lower surfaces of the core laminate to produce a base laminate. Then, the base laminate is cut to produce a formed body of the capacitor body.
[0034] Next, the formed body of the capacitor body is fired to produce the capacitor body. The maximum temperature during formal firing is 1100°C, the holding time is 10 minutes, and the heating rate is 2000°C / h. A roller kiln is used for firing. Next, the produced capacitor body is reoxidized. The reoxidation treatment conditions are: in a nitrogen atmosphere, the maximum temperature is 950°C, and the holding time is 5 hours.
[0035] The size of the capacitor body obtained was 2 mm×1.2 mm×1.2 mm. The average thickness of the dielectric layer was 2 μm. The average thickness of the internal electrode layer was 0.8 μm. The design value of the electrostatic capacitance of the produced capacitor was set to 11 μF.
[0036] Next, after the capacitor body is barrel-polished, an external electrode paste containing copper powder as the main component is applied to both ends of the capacitor body, and heat-treated at 800°C in a nitrogen atmosphere to form external electrodes. Then, nickel plating and tin plating are formed on the surface of the external electrodes to obtain a capacitor.
[0037] In addition, for a sample with the same composition as sample No. 5, a separate sample was prepared at a heating rate of 10000°C / h during the formal firing. In this case, in the obtained capacitor, the proportion of rare earth element oxide particles that can be confirmed in the dielectric layer is small, but instead, magnesium (magnesium oxide) and manganese oxide (Mn2O3) are confirmed to be contained in the dielectric layer as single element oxide particles. The peak ratio R2O3(111) / BT(110) of the rare earth element oxide particles of this sample in X-ray diffraction is 0.3%.
[0038] In addition, a composite oxide of a rare earth element and titanium oxide (pyrochlore: RE2Ti2O7) was synthesized, and capacitors added with the composite oxide were similarly produced. The capacitors produced using the composite oxide of a rare earth element and titanium oxide (pyrochlore: RE2Ti2O7) are samples No. 8 to 10, 12, 14, 16, 18, and 20 among the samples shown in Table 1.
[0039] Next, the capacitors were evaluated as follows. First, the electrical properties of the capacitors were measured. The capacitance was measured using a capacitance meter (4284A manufactured by Agilent Technologies). The measurement conditions were an AC voltage of 0.5 V and a frequency of 1 kHz. The high temperature load life was maintained at a temperature of 125°C, an applied DC voltage of 40 V, and a condition of 200 hours. The short circuit (resistance of 10 1Ω or less) is considered defective (failure). The heat shock resistance is measured by immersion in a heated solder tank. The temperature of the solder tank is set to a temperature difference of 280°C from room temperature (25°C). The immersion time is 1 minute. After immersion in the solder tank, samples with cracks confirmed are counted as defective.
[0040] The average particle size of the main crystal grains, the shape of the oxide particles, and the average particle size of the oxide particles were determined by the following method using a scanning electron microscope equipped with an analyzer. First, from the cross section of the capacitor body that has been cross-section ground, in the middle of the stacking direction, the central part in the width direction is selected, and an area of 5 μm in the width direction and 5 μm in the thickness direction is selected. Next, the composition of the crystal grains visible in this area is identified. The crystal grains that form the parent phase are barium titanate.
[0041] In addition, oxide particles containing rare earth elements in the form of single-element oxides exist in the parent phase. The diameter D of the oxide particles is calculated as follows. First, a cross section of the dielectric layer is exposed. Next, the exposed cross section is mirror-polished. The cross section of the polished dielectric layer is observed using a scanning electron microscope, and a photograph of a specific area is taken. Next, a region containing oxide particles and 200 to 300 main grains is selected on the photograph. Next, the contours of the multiple oxide particles present in the region are obtained from the photograph by handwriting. The contours of each oxide particle are image-processed, and the area of the circle is calculated based on the contour. Next, the diameter is calculated based on the area of the circle. Next, the average value of the diameter values calculated based on the multiple oxide particles is calculated. In Table 1, this average value is referred to as the average particle size (D RE ) is used to represent the average grain size of the main grains (D BT ) and the average particle size of the pyrochlore grains were also determined in the same manner. RE / D BT ” is the average particle size of the oxide particles (D RE ) and the average particle size of the grains containing barium titanate as the main component (D BT ) ratio.
[0042] In the capacitors corresponding to the present disclosure among the samples prepared, it was confirmed that they had a circular shape ( Figure 3The oxide particles have cross-sectional shapes of more than half of the types of cross-sectional shapes selected from the group consisting of the symbol 11a in FIG. 1 ), polygonal shape (11b), triangular shape (11c), quadrilateral shape (11d), elliptical shape (11e), tumbler shape (11f), arrow shape (11g), concave-convex shape (11h) formed by connecting a neck portion (11ha) and a trunk portion (11hb). In particular, the oxide particles have cross-sectional shapes selected from the group consisting of the polygonal shape (11b), triangular shape (11c), quadrilateral shape (11d), elliptical shape (11e), tumbler shape (11f), arrow shape (11g), concave-convex shape (11h) formed by connecting a neck portion (11ha) and a trunk portion (11hb).
[0043] The content of oxide particles contained in the dielectric layer is expressed as a value obtained by the following method using an X-ray diffraction apparatus. First, the external electrodes are removed from the manufactured capacitor and processed into a state of a capacitor body. Next, the capacitor with the external electrodes removed is crushed and the sample is prepared into a powder state. At this time, the metal components are removed from the powder as much as possible. Next, the obtained powder is subjected to X-ray diffraction. As the peak for obtaining the diffraction intensity ratio, the peak with index (110) is selected for barium titanate, and the peak with index (111) is selected for the oxide particles of the rare earth element. The diffraction intensity ratio is shown in the "Diffraction Intensity Ratio RE2O3(111) / BT(110)" column of Table 1. The diffraction intensity ratio of pyrochlore is also shown in Table 1. The diffraction intensity ratio is in the "Diffraction Intensity Ratio RE2Ti2O7(222) / BT(110)" column of Table 1.
[0044] [Table 1]
[0045]
[0046] The results in Table 1 show that for the samples (samples Nos. 1 to 7, 11, 13, 15, 17, and 19) in which one element was confirmed to exist in the dielectric layer in the form of single element oxide particles, the number of defects in the high temperature load life test was less than 1 in 100. In addition, the number of defects in the heat shock resistance test was also less than 1 in 100.
[0047] Among these samples, samples (Sample Nos. 1 to 3, 5, 6, 11, 13, 15, 17, and 19) having an average particle size of 0.15 μm or more and 0.3 μm or less, which was obtained by converting the contour of the oxide particles into a circle, had an electrostatic capacitance of 10.1 μF or more.
[0048] In addition, for the proportion of oxide particles contained in the dielectric layer, the samples (samples No. 3 to 6, 11, 13, 15, 17 and 19) having an intensity ratio of 1.5% or more and 3% or less, obtained by powder X-ray diffraction of the dielectric layer based on the main peak of barium titanate, showed no defects in the high temperature load life test.
[0049] In addition, in a capacitor in which oxide particles, which are one element existing in the form of a single element oxide in the dielectric layer, also contain magnesium (magnesium oxide) and manganese oxide (Mn2O3) in addition to oxide particles of rare earth elements, the electrostatic capacitance was also 10.1 μF, and the number of failures in the high-temperature load life test was 2 in 100.
[0050] On the other hand, the number of failures in the high temperature load life test of the samples including pyrochlore crystal grains (sample Nos. 8 to 10, 12, 14, 16, 18, and 20) was 3 or more per 100 samples.
[0051] In addition, in the sample (sample No. 21) using unfired yttrium oxide powder as the oxide of the rare earth element, although the composite oxide of the rare earth element (Y) and Si was distributed in the dielectric layer in a dotted manner, the presence of oxide particles of Y2O3 in the form of a single element oxide could not be confirmed. In addition, the number of failures in the high temperature load life test was 5 out of 100.
[0052] The present disclosure may be implemented in the following ways.
[0053] The capacitor disclosed herein comprises a capacitor body in which a plurality of dielectric layers and internal electrode layers are alternately stacked, wherein the dielectric layers are mainly composed of a plurality of crystal grains having barium titanate as a main component, and contain magnesium, a rare earth element, and manganese, wherein at least one of the magnesium, the rare earth element, and the manganese exists in the form of single element oxide particles.
[0054] The present disclosure may be implemented in various other forms without departing from its spirit or main features. Therefore, the foregoing embodiments are merely exemplary in all respects, and the scope of the present disclosure is defined by the claims and is not limited by any specification text. Further, all changes or modifications falling within the scope of the claims are within the scope of the present disclosure.
[0055] Explanation of symbols
[0056] 1. Capacitor body;
[0057] 3. External electrodes;
[0058] 5. Dielectric layer;
[0059] 5A, maternal phase;
[0060] 7. Internal electrode layer;
[0061] 9. Main grain;
[0062] 11. Oxide particles;
[0063] 13. Dihedral grain boundary;
[0064] 15. Grain boundary phase.
Claims
1. A capacitor having a capacitor body in which dielectric layers and internal electrode layers are alternately stacked; The dielectric layer is mainly composed of a plurality of crystal grains having barium titanate as a main component, and contains magnesium, rare earth elements and manganese; At least one of the magnesium, the rare earth element and the manganese does not form a composite oxide with other metal oxides but exists in the form of single element oxide particles; The ratio of the oxide particles contained in the dielectric layer after sintering is 1.5% or more and 3% or less in terms of intensity ratio determined by powder X-ray diffraction based on a main peak of barium titanate. 2 . The capacitor according to claim 1 , wherein the oxide particles have an average particle size calculated by converting the contour of the oxide particles into a circle and is 0.15 μm to 0.3 μm. 3 . The capacitor according to claim 1 , wherein the oxide particles are present in the capacitor body except for the internal electrode layer.
Citation Information
Patent Citations
Laminated ceramic capacitor
JP2011132056A
Multilayer ceramic capacitor and method for production thereof
CN101517672A